Measurement of Ankle Dorsiflexion in Patients with Heel Pain - Shrestha, Praphulla; Chalise, Pralhad Kumar; Mishra, Anil Kumar (Nepal Medical College Journal, 2025)
Plantar and posterior heel pain is a common condition seen in orthopedic outpatient department. Gastrocnemius contracture has been attributed to the cause of heel pain in general. Gastrocnemius contracture can easily be diagnosed by Silfverskiöld test in the outpatient department. A cross-sectional study was performed in 60 patients in Department of Orthopedics and Trauma of Nepal Medical College Teaching Hospital from November 2023 to April 2024 after ethical approval (Ref No. 29-080/081). Measurement of ankle dorsiflexion with digital goniometer and Silfverskiöld test was performed in patients with posterior and plantar heel pain. The mean age of 60 patients with heel pain was 45.28 years (SD 11.21). Out of these, 66.6% had plantar heel pain, 33.3% had posterior heel pain. Eighty percent were female, and 60.0% had left-side involvement. BMI was normal in 35.0%, while 65.0% were overweight or obese. Gastrocnemius contracture affected 33.3% of heels, and 28.3% had isolated gastrocnemius contracture. Radiographs showed plantar heel spurs in 50.0% of cases and posterior calcaneal spurs in 38.3% cases. Our study concludes that reduced ankle dorsiflexion due to gastrocnemius contracture contributes to the development of both plantar and posterior heel pain. Increased body mass index is a very important contributing factor in the causation of both plantar and posterior heel pain.